THE NEED FOR SOCIOLOGICAL RESEARCH ON THE MANAGEMENT AND DEVELOPMENT OF SOCIAL INFRASTRUCTURE IN SMALL TOWNS (Archive of Conferences, 2021)
This article focuses on the need for sociological research on the management and development of social infrastructure in small towns.